تصور مقترح لمشروع الوساطة الأسرية لتخفيف من السلوك العدواني لدى - قيسي, محمد (University of Eloued جامعة الوادي, 2022)
إن الأسرة هي العامل الأول والأساسي في تكوين الكيان المجتمعي والتربوي حيث أنها تساهم في تكوين شخصية الفرد وتعليمه العادات والتقاليد والتربية والدين وكل هده الأمور تقوم بها الأسرة. وفي هذا الصدد قمنا بمشروع التدخل حول الوساطة الأسرية التي تقوم بحل النزاع والخلاف القائم بين الطرفين المتخاصمين وتسوية العلاقات فيما بينها والاحترام والإصغاء المتبادل والابتعاد عن العنف والحديث يكون بالدور كل طرف يطرح وجهة نظره والطرف الآخر يستمع والعكس كدلك وبهذا يخرج الطرفان بقرار مناسب. ومن ثم توصلنا إلى نتيجة مقبولة وهي تحقيق الاتصال والتواصل بين الأسرة والمراهق اد جعل المراهق يخفف من سلوكه العدواني والتحاقه بالدراسة عن بعد وتكوينه مهنيا ونلاحظ هناك تغيير في أفكاره السلبية وجعله يندمج مع أسرته ويشاركهم الحديث واحترام والتقدير المتبادل فيما بينهم كما نجد الأسرة قامت بتغيير أسلوبها من ناحية تغيير طريقة التعامل وتحسينها إلى الأفضل فبهذا حقق المشروع نتائج مرغوب فيها. الكلمات المفتاحية: تصور مقرح. مشروع وساطة أسرية. التخفيف. السلوك العدواني. المراهق المتسرب دراسيا ومهنيا. Abstract: The family is the first and main factor in the formation of the societal and educational entity, as it contributes to the formation of the individual’s personality and education of customs, traditions, education and religion, and all these things are done by the family. In this regard, we have implemented the intervention project on family mediation, which resolves the conflict and the existing dispute between the two opposing parties, settles relations between them, respects and mutual listening, and avoids violence and talks. Each party presents its point of view and the other party listens, and the opposite comes out. The parties have an appropriate decision. And then we reached an acceptable result, which is to achieve communication and communication between the family and the teenager, which made the teenager reduce his aggressive behavior and join the distance study and form him professionally. We also find that the family has changed its approach in terms of changing the way of dealing and improving it for the better. Thus, the project achieved desirable results. key words: sore perception .family mediation project. Mitigation. aggressive behavior. The teenager who dropped out both academically and professionally.
مقال